2015
DOI: 10.1159/000431319
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Significance of Incidental Focal Thyroid Uptake on <sup>18</sup>F-FDG PET Study in a Large Patient Cohort: Retrospective Single-Centre Experience in the United Kingdom

Abstract: Objective: To assess the prevalence and pathological nature of incidental focal thyroid uptake on 18F-FDG (2-[18F]-fluoro-2-deoxy-D-glucose) PET (positron emission tomography) and examine the role of the maximum standardised uptake value (SUVmax) to differentiate benign from malignant thyroid pathology. Material and Methods:18F-FDG PET reports were retrospectively reviewed. Incidental focal tracer uptake in the thyroid was noted in 147 patients (0.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
(62 reference statements)
0
16
1
Order By: Relevance
“…The probability of malignancy varies with different studies, ranging widely from 14 to 66%. [9][10][11][12][13][14][15][16] For most of the studies the subjects were patients with a non-thyroidal primary malignancy and the incidence of thyroid malignancy was considered higher is such population than the general population. Chen et al reported 14% malignancy in a series of 4,803 patients after biopsies of 83% of the incidentalomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The probability of malignancy varies with different studies, ranging widely from 14 to 66%. [9][10][11][12][13][14][15][16] For most of the studies the subjects were patients with a non-thyroidal primary malignancy and the incidence of thyroid malignancy was considered higher is such population than the general population. Chen et al reported 14% malignancy in a series of 4,803 patients after biopsies of 83% of the incidentalomas.…”
Section: Discussionmentioning
confidence: 99%
“…3 PET incidentalomas are divided into diffuse and focal types. [9][10][11][12][13][14][15][16] The incidence of metastatic disease to the thyroid gland ranges from 1.25 to 24%. 4 Diffuse type generally suggests a benign lesion since most cases are autoimmune thyroiditis, 5,6 with rare exceptions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of thyroid ''incidentalomas'' in the general population is increasing, and some require further clinical evaluation to exclude clinically significant thyroid disease. Thyroid incidentalomas have been detected by 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) in up to 10% of patients (2). Thyroid cancer is one clinically important diagnosis to exclude in a patient found to have a thyroid incidentaloma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, focal or diffuse thyroid activity usually corresponds to an anatomic abnormality. The recommended work-up includes a thyroid ultrasound (US), followed by a fine-needle aspiration (FNA) biopsy based on the thyroid nodule features detected by the US because of the high risk of malignancy (8-64%) associated with 18 F-FDG PET-positive thyroid nodules (2,4).…”
Section: Introductionmentioning
confidence: 99%